Foreign competition and the durability of US firm investments. (19th June 2019) - Fromenteau, Philippe; Schymik, Jan; Tscheke, Jan
Abstract: How does the exposure to product market competition affect the investment horizon of firms? We study if firms have an incentive to shift investments toward more short‐term assets when exposed to tougher competition. Based on a stylized firm investment model, we derive a within‐firm estimator using variation across investments with different durabilities. Exploiting the Chinese World Trade Organization (WTO) accession, we estimate the effects of product market competition on the composition of US firm investments. Firms that experienced tougher competition shifted their expenditures toward investments with a shorter durability. This effect is larger for firms with lower total factor productivity.